Relevant Pastoral and Teaching Models in Pentecostal Churches in Indonesia Region I Kupang City - Robi Adison Kause; Ezra Tari; Fenetson Pairikas (MASI Mandiri Edukasi, 2026)
This research analyzes relevant models of pastoring and Bible teaching at the Pentecostal Church in Indonesia (GPdI) Region I, Kupang City. The research problem stems from the phenomenon of congregational spiritual stagnation, characterized by weak prayer lives, limited Bible reading, low service involvement, and teaching that is less contextually relevant amid the challenges of secularization and technology. The research objective is to determine how pastors carry out pastoral duties holistically and to develop teaching strategies that meet the spiritual needs of the congregation. The research method is a qualitative approach grounded in practical theology. Data were collected through observation, interviews, and literature reviews, and analyzed using descriptive-analytical methods. The research results indicate four main dimensions of relevant pastoring: based on divine calling and exemplary leadership; contextual prayer ministry; responsive, relational, and adaptive, integrative within limitations. Furthermore, four relevant teaching points were found: faithfulness to the word as the primary foundation, emphasis on practical application, dependence on the Holy Spirit, and flexibility of methods according to the congregational context. The research concludes that the relevant model is transformative in shaping a Christ-like character within the congregation.